Answer:
B
Step-by-step explanation:
I Think I Got It Right But This Is From A LONG time ago
The simplified form of the expression is ![x^{-45} y^{-42}](https://tex.z-dn.net/?f=x%5E%7B-45%7D%20y%5E%7B-42%7D)
<h3>Simplifying an expression</h3>
From the question, we are to simplify the given expression
The given expression is
![\frac{x^{8}y^{-26} }{x^{14}y^{-5} } \times x^{-39} y^{-21}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B8%7Dy%5E%7B-26%7D%20%20%7D%7Bx%5E%7B14%7Dy%5E%7B-5%7D%20%20%7D%20%5Ctimes%20x%5E%7B-39%7D%20y%5E%7B-21%7D)
The expression can be simplified as shown below
![\frac{x^{8}y^{-26} }{x^{14}y^{-5} } \times x^{-39} y^{-21}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B8%7Dy%5E%7B-26%7D%20%20%7D%7Bx%5E%7B14%7Dy%5E%7B-5%7D%20%20%7D%20%5Ctimes%20x%5E%7B-39%7D%20y%5E%7B-21%7D)
![\frac{x^{8} \times x^{-39} \times y^{-26} \times y^{-21} }{x^{14} \times y^{-5} }](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B8%7D%20%5Ctimes%20x%5E%7B-39%7D%20%5Ctimes%20%20y%5E%7B-26%7D%20%5Ctimes%20%20y%5E%7B-21%7D%20%20%7D%7Bx%5E%7B14%7D%20%5Ctimes%20y%5E%7B-5%7D%20%20%7D)
![\frac{x^{8+-39} \times y^{-26+-21} }{x^{14} \times y^{-5} }](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B8%2B-39%7D%20%5Ctimes%20%20y%5E%7B-26%2B-21%7D%20%20%7D%7Bx%5E%7B14%7D%20%5Ctimes%20y%5E%7B-5%7D%20%20%7D)
![\frac{x^{8-39} \times y^{-26-21} }{x^{14} \times y^{-5} }](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B8-39%7D%20%5Ctimes%20%20y%5E%7B-26-21%7D%20%20%7D%7Bx%5E%7B14%7D%20%5Ctimes%20y%5E%7B-5%7D%20%20%7D)
![\frac{x^{-31} \times y^{-47} }{x^{14} \times y^{-5} }](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B-31%7D%20%5Ctimes%20%20y%5E%7B-47%7D%20%20%7D%7Bx%5E%7B14%7D%20%5Ctimes%20y%5E%7B-5%7D%20%20%7D)
Then,
![\frac{x^{-31} }{x^{14} } \times \frac{ y^{-47} }{ y^{-5} }](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B-31%7D%20%7D%7Bx%5E%7B14%7D%20%7D%20%5Ctimes%20%5Cfrac%7B%20y%5E%7B-47%7D%20%7D%7B%20y%5E%7B-5%7D%20%7D)
![x^{-31-14} \times y^{-47--5}](https://tex.z-dn.net/?f=x%5E%7B-31-14%7D%20%5Ctimes%20y%5E%7B-47--5%7D)
![x^{-31-14} \times y^{-47+5}](https://tex.z-dn.net/?f=x%5E%7B-31-14%7D%20%5Ctimes%20y%5E%7B-47%2B5%7D)
![x^{-45} \times y^{-42}](https://tex.z-dn.net/?f=x%5E%7B-45%7D%20%5Ctimes%20y%5E%7B-42%7D)
![x^{-45} y^{-42}](https://tex.z-dn.net/?f=x%5E%7B-45%7D%20y%5E%7B-42%7D)
Hence, the simplified form of the expression is ![x^{-45} y^{-42}](https://tex.z-dn.net/?f=x%5E%7B-45%7D%20y%5E%7B-42%7D)
Learn more on Simplifying an expression here: brainly.com/question/2320607
#SPJ1
12.25 is the scale factor if the pre image is 12 and the image is 147
Answer:
(f + g)(x) = I2x + 1I + 1 ⇒ C
Step-by-step explanation:
Let us solve the question
∵ f(x) = I2x + 1I + 3
∵ g(x) = -2
→ We need to find (f + g)(x), which means add the two functions
∵ (f + g)(x) = f(x) + g(x)
→ Substitute the right side of each function on the right side
∴ (f + g)(x) = I2x + 1I + 3 + (-2)
→ Remember (+)(-) = (-)
∴ (f + g)(x) = I2x + 1I + 3 - 2
→ Add the like terms in the right side
∵ (f + g)(x) = I2x + 1I + (3 - 2)
∴ (f + g)(x) = I2x + 1I + 1
V = S*h
h = V/S = 250*pi / 50*pi = 5 m